Audience entrainment during live contemporary dance performance: physiological and cognitive measures - Bachrach, Asaf; Fontbonne, Yann; Joufflineau, Coline; Ulloa, José Luis (Frontiers in Human Neuroscience, 2015)
Perceiving and synchronizing to a piece of dance is a remarkable skill in humans. Research in this area is very recent and has been focused mainly on entrainment produced by regular rhythms. Here, we investigated entrainment effects on spectators perceiving a non-rhythmic and extremely slow performance issued from contemporary dance. More specifically, we studied the relationship between subjective experience and entrainment produced by perceiving this type of performance. We defined two types of entrainment. Physiological entrainment corresponded to cardiovascular and respiratory coordinated activities. Cognitive entrainment was evaluated through cognitive tasks that quantified time distortion. These effects were thought to reflect attunement of a participant’ internal temporal clock to the particularly slow pace of the danced movement. Each participant’ subjective experience—in the form of responses to questionnaires—were collected and correlated with cognitive and physiological entrainment. We observe: (a) a positive relationship between psychological entrainment and attention to breathing (their own one or that of dancers); and (b) a positive relationship between cognitive entrainment (reflected as an under-estimation of time following the performance) and attention to their own breathing, and attention to the muscles’ dancers. Overall, our results suggest a close relationship between attention to breathing and entrainment. This proof-of-concept pilot study was intended to prove the feasibility of a quantitative situated paradigm. This research is inscribed in a large-scale interdisciplinary project of dance spectating (labodanse.org).